Safety and Efficacy of Vacuum Assisted Thrombo-Aspiration in Patients with Acute Lower Limb Ischaemia: The INDIAN Trial. (May 2021) - de Donato, Gianmarco; Pasqui, Edoardo; Sponza, Massimo; Intrieri, Francesco; Spinazzola, Angelo; Silingardi, Roberto; Guzzardi, Giuseppe; Ruffino, Maria Antonella; Palasciano, Giancarlo; Setacci, Carlo; ,; Jannello, Antonio; et al.
Abstract : Objective: The aim was to evaluate the short term safety and effectiveness of the Penumbra/Indigo aspiration thrombectomy Systems (Penumbra Inc.) in patients with acute lower limb ischaemia. (ALLI). Recently, endovascular vacuum assisted thrombectomy devices, similar to those used in the management of acute ischaemic stroke, have become available for peripheral arteries, but data are still scarce. Methods: To assess vessel patency, a modified Thrombolysis in Myocardial Infarction (TIMI) classification, called TIPI (Thrombo-aspiration In Peripheral Ischaemia), is proposed. The TIPI flow is assessed at presentation, immediately after treatment with the study device, and after all adjuvant procedures. The primary outcome is the technical success of the thrombo-aspiration with the investigative system, defined as near complete or complete revascularisation TIPI 2 – 3. Safety and clinical success rate were collected at one month. Results: One hundred and fifty patients were enrolled. The mean age was 72.4 years and 73.3% were male. Rutherford grade on enrolment was I in 16%, IIa in 40.7%, and IIb in 43.3% with a mean ankle brachial index of 0.19. Primary technical success (TIPI 2 – 3 flow) was achieved in 88.7% of patients. Adjunctive procedures included angioplasty/stenting of chronic atherosclerotic lesions ( n  = 39), thrombolysis ( n  = 31), covered stenting ( n  = 15), and supplementary Fogarty embolectomy ( n  = 6). After all interventions, assisted primary technical success was 95.3% (TIPI 2 – 3 in 143/150). No systemic bleeding complications or device related serious adverse events were reported. At one month follow up, one death, and one below the knee amputation were recorded. Primary patency was 92% (138/150), and the re-intervention rate was 7.33%, resulting in an assisted primary and secondary patency of 94% and 99.33%, respectively. Conclusion: Results from the INDIAN registry reveal that mechanical thrombectomy using the Indigo system is safe and effective for revascularisation of ALLI as a primary therapy.